EFEK HARDINESS TERHADAP PERILAKU MENCONTEK MELALUI EFIKASI DIRI SISWA SEKOLAH MENENGAH ATAS - Widya Khairunissa Hidayat; Herlina Hasan; Lira Fessia Damaianti (Departemen Psikologi Universitas Pendidikan Indonesia, 2018)
This study aims to find out the influence of hardiness personality on cheating behavior through self-efficacy. Sample of study consist of 319 students of a high school. The instrument used is hardiness scale from Creed, Conlon, and Dhaliwal (2013), cheating behavior questionnaire which is adopted from Saddam (2016), and self-efficacy questionnaire from Schwarzel and Jarusalem (1995). This study use quantitative method with path analysis to find out cause-effect relation and involve self-efficacy variable as mediator variable. The results of study is significant negative influence of hardiness personality on cheating behavior,found significant influence of hardiness personality on self-efficacy, and Self-efficacy variable statistically can become significant mediator variable for hardiness personality toward cehating behavior. Therefore, hardiness personality becocme one contribution to influence students’ behavior in doing all tasks assigned and self-efficacy possessed also can contribute to students to be confident in finishing the tasks assigned at school.